ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMA - Andhita Rachmawati; Alpha Galih Adirakasiwi (IKIP Siliwangi, 2021)
The research aim to analyzes the ability problem solving mathematical students. a method of research used is descriptive qualitative .The subject of study is 27 students XI at one state senior high school in kabupaten bogor . Technique data collection with use of the instruments tests the ability of problem solving mathematical matter system of equations linear two variables .Technique data analysis three steps, those check their answers students , provides the data test , and draw conclusions the research .The results from the study is the percentage of achievement the ability problem solving mathematical students at the understanding a problem of 30 % , at devising a plan of 52 % , at carrying out of 52 % and looking back of 50 %. This shows that the problem solving mathematically students are on medium category.